Are spontaneous activity and supraspinal control co-responsible for functional development of the generator of embryonic motility? - Sedlácek, J (Physiologia Bohemoslovaca, 1989)
The effect of chronic administration of phenobarbital (from the 4th to the 16th day of incubation) combined with chronic spinal decentralization (decapitation at stage 11-13) on the development of spontaneous motor activity (recorded on the 17th day of incubation) was studied in 4 to 17-day-old chick embryos. 1. Combination of the two experimental treatments led to summation of their negative effect on development; spontaneous motor activity fell to 15.2% of the control value (to 26.9% after the isolated administration of phenobarbital and to 30.5% after isolated decapitation). 2. Metrazol activation of motor activity (100 mg/kg egg weight) after combination of the two factors was relatively no different from the results after their isolated use. 3. The acute administration of GABA (100 mg/kg e.w.) likewise induced relatively the same depression of spontaneous motility as after isolated chronic decapitation and the isolated chronic administration of phenobarbital. The results confirm the hypothesis of the significance of spontaneous activity of the spinal motoneurones for their survival and their actual functional development during the embryonic period.
Keywords: fenobarbital; Chick Embryo; Animals; Pentylenetetrazole; pohybová aktivita; Motor Activity; Motor Neurons; Central Nervous System; pentylentetrazol; zvířata; centrální nervový systém; Phenobarbital; GABA; kuřecí embryo; gamma-Aminobutyric Acid; motorické neurony